Teacher Competence Based on the Gospel of Matthew - Ana Lestari Uriptiningsih; Muner Daliman (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2022)
Christian education is part of many types of ministry that are essential in all Christ-centered learning activities. But there are still some Christian Education teachers who consider teaching in this field only done because of the work obligation factor. Matthew 28:20 puts pressure on the word